Mediation of Work Motivation: The Impact of Talent Management and Transformational Leadership on Employee Performance - Nursaid Nursaid; Feti Fatimah; Nurul Qomariah; Mu'ah Mu'ah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Competition in the education industry is currently increasing, so every educational organization must prepare human resources that can face increasing challenges. This study aims to determine and analyze the impact of talent management and transformational leadership on lecturer performance with motivation as an intervening variable at the University of Muhammadiyah Jember. The population in this study were all lecturers who teach at UM Jember, both DPK and Persyaritan lecturers, totaling 294 lecturers. The sample was determined using the Slovin formula, resulting in a total of 71 lecturers. Each lecturer had the opportunity to become a respondent where the questionnaire was distributed via Google Form. Analysis of respondent descriptions was carried out using descriptive statistics. Validity and reliability tests were also conducted to test the measuring instrument used, namely the research questionnaire compiled based on indicator variables. Smart PLS was used to test the research hypothesis. The results of the study found that talent management did not affect work motivation. Leadership did affect work motivation. Talent management did affect lecturer performance. Meanwhile, transformational leadership did not affect lecturer performance, while work motivation did affect lecturer performance.